Effect of the compound bacterial agent on microbial community of the aerobic compost of food waste. (19th October 2021) - Lu, T.; Yang, Y.; Feng, W.J.; Jin, Q.C.; Wu, Z.G.; Jin, Z.H.
Abstract: In our study, we used 16SrRNA and ITS to investigate the microbial community composition and the effect of compound bacterial agent on the microbial community composition in the aerobic composting process of food waste (FW). At the bacterial level, the main phyla of Group A (compost naturally) were Proteobacteria and Firmicutes, and the main species were Pseudomonas_sp._GR7, Bacillus licheniformis and Pediococcus acidilactici . The main phyla of Group B (compost with compound bacterial agent) were Proteobacteria, Firmicutes and Streptophyta, and the main species were Klebsiella pneumoniae, Cronobacter sakazakii, Macrococcus caseolyticus, Enterococcus faecalis, Citrobacter freundii and Bacillus velezensis . It is worth noting that M. caseolyticus may be able to improve the effect of odour which is an important sensory index during aerobic composting. At the fungal level, the main phylum of both Groups A and B was Ascomycota, and the main species of Group A were Paecilomyces variotii, Byssochlamys spectabilis and Aspergillus fumigatus . The main species of Group B were Ogataea polymorpha and Millerozyma farinosa . Finally, the degradation rate of Group B was 81% that was about 15% higher than that of Group A, indicating that the compound bacterial agent could effectively improve the degradation rate and the composting process, while the low abundance of the compound bacterial agent in the composting process might be due to the small initial addition or the inhibition of other bacteria or fungi in the composting process. Abstract : Significance and Impact of the Study: Micro‐organisms play an important role in aerobic composting of food waste (FW) which has a good prospect of recycling; in our study, we used 16SrRNA and ITS to explore the effect of added bacteria on the aerobic composting of FW, finding that the FW can be decomposed better with our compound bacterial agent so that the added value of FW can be utilized more comprehensively.